2018
DOI: 10.2298/fil1812319m
|View full text |Cite
|
Sign up to set email alerts
|

On pseudo-valuations on BCK-algebras

Abstract: In this paper, we study some properties of pseudo-valuations and their induced quasi metrics. The continuity of operation of a BCK-algebra was studied with topology induced by a pseudo-valuation. Moreover, we show that product of finite number of this pseudo metric spaces is a pseudo metric space. Also, we prove that if a BCK-algebra X has a pseudo-valuation, then every quotient space of X has a pseudo metric. The completion of this spaces has been investigated in the present study. 2. Preliminaries 2.1. BCK-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In [1], Busneag defined pseudo-valuations on Hilbert algebras and proved that every pseudo-valuation induced a pseudo-metric. Using this model, in [4], [5], [7], [11], [12], [14], [15], [16] is introduced the notion of pseudo-valuation on BCK, BCI, BCC algebras and several properties are discussed.…”
Section: Introduction and Basic Resultsmentioning
confidence: 99%
“…In [1], Busneag defined pseudo-valuations on Hilbert algebras and proved that every pseudo-valuation induced a pseudo-metric. Using this model, in [4], [5], [7], [11], [12], [14], [15], [16] is introduced the notion of pseudo-valuation on BCK, BCI, BCC algebras and several properties are discussed.…”
Section: Introduction and Basic Resultsmentioning
confidence: 99%
“…Jun, Lee and Song analyzed in article [8] several types of quasi-valuation maps on BCK -algebra and their interactions. Also, Mehrshad and Kouhestani were interested in pseudo-valuations on BCK -algebra [10]. Jun, Ahn and Roh.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the concept of pseudo-valuation in R 0 -algebras, Yang and Xin [7] characterized pseudo pre-valuations on EQ-algebras. Mehrshad and Kouhestani studied Pseudo-Valuations on BCK-Algebras [8]. Pseudo-valuations on a BCC-algebra was introduced by Jun et al [9], where they have shown that binary operation in BCC-algebras is uniformly continuous.…”
Section: Introductionmentioning
confidence: 99%